Comparison of Sacral Nerve Stimulation (SNS) and Posterior Tibial Nerve Stimulation (TNS) for Treatment of Fecal Incontinence: Literature Review and Meta-analysis - Tumasonis, Rytis; Petkevičius, Arūnas; Švagždys, Saulius (Lietuvos chirurgija, 2021)
Aim. To evaluate and compare effectivenes of sacral and posterior tibial nerve stimulation for treating fecal incontinence. Methods. Systematic literature review was performed to compare sacral and posterior tibial nerve stimulation effectiveness. Research was performed in “Medline” database, using the “PubMed” website. English or lithuanian articles, published between 2008 and 2019, were included in our study. Results were described to assess the effect of interventions in each analysed article. We included 7 articles into meta-analysis. Articles compared the effectiveness of sacral or posterior tibial nerve stimulation with control groups or other treatment methods for managing fecal incontinence. Cochrane guidelines were used to perform this meta-analysis. Results. The results of meta-analysis suggests that sacral neuromodulation is superior to posterior tibial nerve stimulation to treat fecal incontinence compared to control groups or other treatments. Literature also suggest that after comparing these methods directly, sacral neuromodulation is superior to treat fecal incontinence a. Conclusion. Sacral neuromodulation is superior posterior tibial nerve stimulation to treat temporary or chronical fecal incontinence than and can be used as an alternative for surgical interventions.